2016
DOI: 10.1590/s0080-623420160000700004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hope among women with breast cancer during chemotherapy

Abstract: Objective:Identifying the predictors of hope in patients with breast cancer during chemotherapy treatment. Method: A prospective longitudinal study. The sample was composed of 122 women who responded to the instruments of hope, anxiety and depression, coping, fatigue, religiosity and self-esteem in the first and last cycle of chemotherapy. These variables were used in adjusting the logistic regression model that characterized multivariate statistics, allowing identification of predictor variables. Result: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
1
7
1
5
Order By: Relevance
“…18 On the other hand, pain, depression, self-esteem, and functional status were found to be the predictors of hope in cancer patients. 19 Another study demonstrated that anxiety, depression, effects and symptoms of renal disease, and mental health dimension of quality of life were the predictors of hope in hemodialysis patients. 20 As maintained above, some studies have evaluated the predictors of hope in chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…18 On the other hand, pain, depression, self-esteem, and functional status were found to be the predictors of hope in cancer patients. 19 Another study demonstrated that anxiety, depression, effects and symptoms of renal disease, and mental health dimension of quality of life were the predictors of hope in hemodialysis patients. 20 As maintained above, some studies have evaluated the predictors of hope in chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Foi possível observar que os dados sociodemográficos não influenciaram diretamente na esperança das pacientes avaliadas, embora haja estudos que tenham encontrado associação significativa com a renda (7) .…”
Section: Discussionunclassified
“…Não foi observada variação da esperança ao longo do tempo de tratamento. No entanto, em estudo realizado com mulheres da cidade de São Paulo em tratamento para o câncer de mama, a esperança foi observada de forma dependente durante todo o processo de tratamento, apresentando-se de forma positiva quando a paciente se encontrava em um bom estado clínico e proximidade da cura, e negativa diante do início do tratamento, atraso no diagnóstico, com alterações psicológicas e aparecimento dos efeitos adversos do tratamento (7) .…”
Section: Discussionunclassified
See 2 more Smart Citations